Electron Microscopical Studies on Lymph node of Pati duck (Anas platyrhynchos domesticus) of Assam at Different Stages of Development - Deka, A.; Mahanta, J. D.; Perumal, P. (International Journal of Bio-resource and Stress Management, 2020)
The present investigation was conducted on the histomorphological, histo-chemical and scanning electron microscopical observation on the lymph node of Pati duck of Assam at different stages of development. Structure of the cervical and lumber lymph node of Pati duck revealed the same structure in histomorphological observation. The lymph node was surrounded by a thin connective tissue capsule. The trabeculae which were arisen from the capsule divided the lymph node into number of irregular compartments. The trabeculae became distinct with the advancement of age. The parenchymatus part of these lymph node consisted of inner cortex and outer medulla along the cortical and medullary sinuses. The cortex of lymph node was occupied by numerous follicles with different shape. These lymphoid follicles were surrounded by very thin layer of capsule. The medulla of these lymph node consisted of medullary sinuses and medullary cords. The medullary sinuses were larger compared to the cortical sinuses. The medulla was loosely arranged in week 4th of age of Pati duck whereas in week 16th, 24th and 42nd of age, it became compact. Histochemicaly, the lymphatic nodule of lymph node showed intense reaction for acid phosphatase at week 42nd of age of Pati duck whereas lymphatic nodule of lymph node showed strong reaction for adenosine tri-phosphatase. In scanning electron microscopy, the lymph node of Pati duck were surrounded by very thin capsule and it contained numerous connective fibers. Medulla of the lymph node was peripherally located whereas cortex was situated centrally. The lymph node contained connective tissue fibers where lymphocytes were attached.